DIRECTION FOR CITY FOREST DEVELOPMENT AS AN OPEN SPACE IN SOUTH TANGERANG CITY (Case Study: BSD City Urban Forest Setu District) - Fuji Widyawati, Laili; Galih Hermayadi, Eggy; Ariesta Kirana Sari, Dayu; Supriadi, Hari (International Journal of Psychosocial Rehabilitation, 2020)
BSD City City Forest is one of the Green Open Spaces in the Setu District Area, South Tangerang City. The urban forest which is located on Tekno Widya Street is included in the category of natural tourism. There are many facilities in it such as jogging tracks, children’s playgrounds and many ornamental plants in it. It can be seen from its development that BSD City Urban Forest has potential advantages to be developed into the tourism sector, but the condition of BSD City Urban Forest is also underdeveloped due to the lack of supporting facilities. The purpose of this study is to determine the direction of the development of the BSD City Urban Forest in order to maximize the potential and overcome the problems that are owned by the BSD City Urban Forest. The method used in this research is qualitative and quantitative methods and uses development direction analysis to determine the development strategy to be carried out in BSD City Urban able to make BSD City Urban Forests as an open space that is beneficial for the people of South Tangerang City and surrounding areas.